THE EPIC “QIRONXON” IN ANCIENT TURKIC FOLK EPIC TRADITION (World Bulletin of Education and Learning, 2025)
This scientific article is devoted to the analysis of the historical, artistic and cultural significance of the epic poem "Qironxon", one of the high examples of the oral creativity of the Uzbek people. The work comprehensively covers the inextricable connection of the epic poem with ancient Turkic epic traditions, its formation and stages of development.
Keywords: “Qironxon” epic, heroic epic, epic poetry of the Turkic peoples, folklorism in epic poetry, historical memory.